2020
DOI: 10.35940/ijeat.c5317.029320
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Understanding of Airflow in Non Air conditioned Bus Coaching System

Niranjana S J,
Shivalingapa S Kubsad,
Ravichandran G
et al.

Abstract: Bus is a Major mode of transport in India and the passenger safety is significant during the travel. This Comprehensive comprehension on the literatures available discusses various parameters used to improve the Vehicle Design, Safety, Fuel Efficiency and decrease in drag of the vehicle. The outcomes obtained from CFD investigation is tabulated, and the exploratory outcomes obtained from aerodynamic tests are contrasted and numerical examination and the outcomes are additionally incorporated. The impact of tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The non-AC bus is a major mode of transport in developing countries. During the journey passengers, comfort plays a vital role by Niranjan et al [1]. The uneven airflow inside a non-AC bus may cause discomfort on the passenger.…”
Section: Introductionmentioning
confidence: 99%
“…The non-AC bus is a major mode of transport in developing countries. During the journey passengers, comfort plays a vital role by Niranjan et al [1]. The uneven airflow inside a non-AC bus may cause discomfort on the passenger.…”
Section: Introductionmentioning
confidence: 99%
“…Suffocation causes breathing interruption with oxygen deprivation. 1 To overcome this issue, it is required to design the non-AC bus in such a way that there should be uniform flow of air within the coach. 2 Kale et al 4 concluded that the air entering from the rare window and door, exit from the front window at one-tenth of the speed of the vehicle.…”
Section: Introductionmentioning
confidence: 99%